Seeing the Offenders' Perspective Through the Eye-Tracking Device: Methodological Insights From a Study of Shoplifters. (November 2015) - Jacques, Scott; Lasky, Nicole; Fisher, Bonnie S.
This article examines the utility of a novel tool for conducting offender-based research: the "eye-tracking device" (ETD), which is designed to identify what a person sees in the center of his or her vision. First, we review prior research using the ETD. Second, we detail the advantages and troubles we encountered when using it to study simulated shoplifting in retail outlets among 39 active offenders. Benefits of using the ETD include video recording what participants look at, which may serve as quantitative or qualitative data, and, when coupled with a questionnaire, the video footage may be used as a memory prompt and source of verification. Thus, using the ETD should reduce two sources of measurement bias: participants' limited recall and intentional fabrication. However, limitations of the ETD are that it may inaccurately record what participants see in their peripheral vision and its physical structure makes some participants feel more inconspicuous than usual, both of which are pertinent to criminals' attempts to avoid apprehension. The peripheral vision problem limits the quantitative output's validity, whereas the physical structure concern potentially diminishes the generalizability of results. We conclude by discussing the implications of our findings for theory and research.